Investigation Genetic Causes Of Hereditary Intellectual Disability in Ahvaz (2011-2012) - Saeedeh Akbari-Mobarakeh; Elinaz Akbari-Azar; Mohammad Reza Ebrahimpour; Hossein Najm-Abadi; Kimia Kahrizi (University of Social Welfare and Rehabilitation Sciences, 2013)
Objective: Intellectual Disability (ID) characterize by significant limitations both in intellectual functioning and in adaptative behavior, originates before the age of 18. Over 70% of severe to profound intellectual disabilities (ID) caused by genetic factors. The aim of this study was to investigate genetic causes of ID in fourty Ahvazi families and provide information for genetic counseling, carrier detection, and prenatal diagnosis. Materials & Methods: In collaboration with Welfare Organization of Khuzestan Province, a total of 183 ID families from Ahwaz were investigated from which 40 (62 male and 42 female) families whose ID had been confirmed by psychiatrist and had more than one affected individual were selected for molecular analysis. Blood samples were collected from all normal and affected individuals in each family on EDTA pre-coated tubes. Thorough clinical characterization, dysmorphism examinations, karyotype analysis were carried out for all of the patients. Results: Three out of 40 (7.5%) families had full mutation of Fragile X syndrome. No chromosomal abnormalities were identified. Metabolic screening revealed none of families had metabolic disorder. None of three families with primary microcephaly showed linkage to any of the seven known MCPH loci. Conclusion: The most common causes of ID in Ahvaz was Fragile X syndrome and Autosomal Reccesive Primary Microcephaly with the frequency of (7.5%). It seems that autosomal reccesive primary microcephaly is a relatively common heterogenous condition in Ahvaz.